2012
DOI: 10.1371/journal.pone.0050449
|View full text |Cite
|
Sign up to set email alerts
|

Association between MLH1 -93G>A Polymorphism and Risk of Colorectal Cancer

Abstract: BackgroundThe -93G>A (rs1800734) polymorphism located in the promoter of mismatch repair gene, MLH1, has been identified as a low-penetrance variant for cancer risk. Many published studies have evaluated the association between the MLH1 -93G>A polymorphism and colorectal cancer (CRC) risk. However, the results remain conflicting rather than conclusive.ObjectiveThe aim of this study was to assess the association between the MLH1 -93G>A polymorphism and the risk of CRC.MethodsTo derive a more precise estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(40 reference statements)
2
7
0
Order By: Relevance
“…38 Rs1800734 encodes for a G to A transition at −93 from the transcription start site within the promoter region and it falls within NF-IL6 and GT-IIB transcription factor binding sites. The polymorphism has been associated with promoter methylation and gene silencing 39,40 and a meta-analysis by Wang et al 41 reported that carriers of the A-allele are at increased risk of colorectal cancer, in agreement with the present results. The association was even stronger among cases positive for MSI.…”
Section: Discussionsupporting
confidence: 92%
“…38 Rs1800734 encodes for a G to A transition at −93 from the transcription start site within the promoter region and it falls within NF-IL6 and GT-IIB transcription factor binding sites. The polymorphism has been associated with promoter methylation and gene silencing 39,40 and a meta-analysis by Wang et al 41 reported that carriers of the A-allele are at increased risk of colorectal cancer, in agreement with the present results. The association was even stronger among cases positive for MSI.…”
Section: Discussionsupporting
confidence: 92%
“…30,31 The most prominent result of genetic studies is the role of mutation in Lynch syndrome (MSH2 and MLH1) and the future development of CRC from previous studies. 32,33 The increased risk for the XRCC1 and BMP4 gene mutations is comparable with a previous review. 34,35 The role of a genetic mutation in the 8q23.3 and 15q13.3 loci is a novel finding that might need future research.…”
Section: Discussionsupporting
confidence: 84%
“…Compared with the similar metaanalysis about MLH1 c. -93G>A polymorphism and CRC, it is the one comprising most studies and consisting of largest population, and the results tended to be more exact and reliable. In 2012, Wang et al (2012) reported that MLH1 c. -93G>A polymorphism was related to increased risk of CRC. However, they only involved six studies, and the ethnicity was just European and Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wang et al (2012) concluded that the MLH1 -93G>A substitution altered promoter function, reduced MMR system activity and was associated with increased risk of CRC. However, Pan et al (2011) could not offer persuasive evidence that allele A was a risk factor for CRC.…”
Section: Introductionmentioning
confidence: 99%